Effect of Adjunctive Aripiprazole on Sexual Dysfunction in Schizophrenia: A Preliminary Open-Label Study - Fujioi, J.; Iwamoto, K.; Banno, M.; Kikuchi, T.; Aleksic, B.; Ozaki, N. (Pharmacopsychiatry, 2017)
Introduction: Although adjunctive aripiprazole improves hyperprolactinemia, sufficient evidence for its effects on sexual dysfunction has not been obtained. We assessed the usefulness of adjunctive aripiprazole for schizophrenia with sexual dysfunction.Methods: 22 Japanese schizophrenia patients with antipsychotic-induced hyperprolactinemia and sexual dysfunction were enrolled, and 19 of them completed the study. Aripiprazole was administrated in a flexible titration schedule to participants according to the judgment of each doctor, and patients were followed for 24 weeks. Serum prolactin, Clinical Global Impression Scales-Severity (CGI-S), and Nagoya Sexual Function Questionnaire (NSFQ) were measured at baseline and at 4, 8, 12, and 24 weeks.Results: Prolactin at week 4 and later was significantly lower than that at baseline. Compared to baseline, we observed a significant improvement in total sexual dysfunction as measured by NSFQ at week 8 and later. In males, erectile dysfunction was significantly reduced at week 24. In females, menstrual irregularity and galactorrhea were significantly reduced at week 24. CGI-S did not significantly change.Discussion: Although the small sample size is a limitation in this study, adjunctive aripiprazole may be useful treatment for sexual dysfunction including hyperprolactinemia in schizophrenia.
Keywords: adjunctive treatment; aripiprazole; hyperprolactinemia; schizophrenia; sexual dysfunction